Development of the Usage of E‑services in Households, by Voivodship: a Cluster Analysis - Kaczmarczyk, Paweł (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The aim of this work is to assess the development of voivodships in terms of the usage of e‑services (e‑government, e‑commerce, e‑health, etc.) in households, in comparison with the research on the overall ICT usage in households, in voivodships. The results of both of these studies enabled the verification of the thesis that the higher the level of overall ICT usage in households, in a given voivodship, the higher the level of e‑services usage in these households. In the theoretical part of the work, the rationale for the research was presented. Therefore, the importance of the usage of e‑services in households, for building an information society and consequently knowledge‑based economy, has been described. The research methodology also included: linear ordering methods (Hellwig’s method, methods that are non‑based on the pattern of development), agglomerative hierarchical clustering method (Ward’s method), and optimisation clustering method (the k‑means method) have been discussed. The empirical part of the work involves presentation of the research results. Data from the year 2017, provided by the Central Statistical Office of Poland, was used. Within the framework of the usage of e‑services in households (26 variables), the rankings of voivodships were created and the clusters of voivodships were detected. The obtained rankings and clusters of voivodships served to compare and assess voivodships in the analysed year. In the light of the results relating to the usage of the e‑services, the results of ordering and clustering of voivodships within the framework of overall ICT usage in households (27 variables) were obtained. Then, the verification of the assumed thesis was conducted.